Corticotropin-releasing hormone induces depression-like changes of sleep electroencephalogram in healthy women. (December 2016) - Schüssler, P.; Kluge, M.; Gamringer, W.; Wetter, T.C.; Yassouridis, A.; Uhr, M.; Rupprecht, R.; Steiger, A.
Highlights: We investigated the effects of pulsatile administration of corticotropin-releasing hormone (CRH) on sleep EEG and the secretion of cortisol and growth hormone (GH) in healthy young women. After CRH, wakefulness was increased during the total night. During the first third of the night, REM sleep and stage 2 sleep increased and stage 3 sleep decreased. After CRH, cortisol concentration was elevated during the first and second third of the night. Similar to previous findings in men, CRH administration mimics some depression-like changes of sleep endocrine activity in women. Abstract: We reported previously that repetitive intravenous injections of corticotropin-releasing hormone (CRH) around sleep onset prompt depression-like changes in certain sleep and endocrine activity parameters (e.g. decrease of slow-wave sleep during the second half of the night, blunted growth hormone peak, elevated cortisol concentration during the first half of the night). Furthermore a sexual dimorphism of the sleep-endocrine effects of the hormones growth hormone-releasing hormone and ghrelin was observed. In the present placebo-controlled study we investigated the effect of pulsatile administration of 4 × 50 μg CRH on sleep electroencephalogram (EEG) and nocturnal cortisol and GH concentration in young healthy women. After CRH compared to placebo, intermittent wakefulness increased during the total night and the sleep efficiency index decreased. During the first third of the night, REM sleep and stage 2 sleep increased and sleep stage 3 decreased. Cortisol concentration was elevated throughout the night and during the first and second third of the night. GH secretion remained unchanged. Our data suggest that after CRH some sleep and endocrine activity parameters show also depression-like changes in healthy women. These changes are more distinct in women than in men.